Finance and Development, March 1977. (Finance and Development; Finance and Development ;, 1977)
This paper highlights that 1976 was an important year for the IMF. With the end of 1976, the IMF closed its books on a year of virtually unprecedented activity. It launched the New Year with a USD 3.9 billion stand-by arrangement for the United Kingdom, the largest ever made for a member country. The outlook at the beginning of 1977 suggests another busy year ahead for the IMF. The proposed second amendment to the IMF's Articles of Agreement and the increase in members' quotas are expected to go into effect before the end of the year.